Synthesis and Characterization of Nanocube Cu2O Thin Film at Room Temperature for Methylene Blue Photodegradation Application - Muhamad Athariq; Muhammad Raihan Rauf; Ikhfa Wiqoy Khairany; Intan Fadia Adani; Mega Gladiani Sutrisno (Pusat Inovasi Sains, 2023)
Methylene Blue is a synthetic dye with a complex structure thus making it hard to decompose naturally. Among the decomposition methods of synthetic dyes is photodegradation using a semiconductor material. In this study, Cu2O semiconductor nanoparticle has been synthesized on the surface of conductive substrate indium tin oxide using the electrodeposition method at room temperature. The X-ray diffractometer analysis provides information on the presence of Cu2O in the sample and the shape of the Cu2O crystal system which is a nanocube. Scanning electron microscopy with energy-dispersive X-ray spectroscopy provides distribution mapping information based on the morphology and atomic composition of the sample. Impedance measured a maximum resistance to charge transfer value of 2500 Ω. Photodegradation test towards methylene blue achieved a percent of degradation was 62.00% for 120 minutes under visible light irradiation with initial and final absorbance values of 1.56351 abs and 0.896875 abs respectively.